Impact of Summer Heat Stress on Oxidative Status, Inflammatory Biomarkers, Acute Phase Proteins and Reproductive Performance in Awassi Ewes: Development of a Heat Stress Index for Fertility Prediction (Indian Journal of Animal Production and Management, 2025)
Background: Heat stress severely compromises reproductive efficiency in sheep, causing substantial economic losses in arid regions. However, no comprehensive study has integrated oxidative, inflammatory, and acute phase biomarkers with reproductive outcomes to develop predictive tools for fertility assessment in Awassi ewes. Objective: This study aimed to evaluate the effects of seasonal heat stress on oxidative status, inflammatory cytokines, acute phase proteins (APPs), and reproductive performance, and to develop a Heat Stress Index (HSI) for predicting conception failure in Awassi ewes. Methods: One hundred twenty multiparous Awassi ewes (3–5 years, 52 ± 4 kg, BCS 2.5–3.0) were allocated to four groups based on breeding season: Thermoneutral (TN, October–November, THI < 72), Mild Heat Stress (MHS, April–May, THI 72– 79), Moderate Heat Stress (MDHS, June–July, THI 80–84), and Severe Heat Stress (SHS, August, THI ≥ 85). Blood samples were analyzed for cortisol, progesterone (P₄), estradiol (E₂), luteinizing hormone (LH), follicle-stimulating hormone (FSH), malondialdehyde (MDA), total antioxidant capacity (TAC), superoxide dismutase (SOD), glutathione peroxidase (GPx), heat shock protein 70 (HSP70), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), haptoglobin (Hp), and serum amyloid A (SAA). Reproductive parameters included estrus response, conception rate, and embryonic loss. ROC analysis and logistic regression were performed. Results: Severe heat stress markedly elevated (P < 0.05) cortisol (12.45 → 38.72 ng/mL), MDA (1.62 → 4.85 nmol/mL), HSP70 (2.45 → 12.86 ng/mL), IL-6 (38.5 → 118.4 pg/mL), and SAA (6.82 → 32.56 μg/mL), while depleting antioxidant defenses and suppressing reproductive hormones. Conception rate declined from 85.7% (TN) to 32.1% (SHS), with embryonic loss increasing from 8.3% to 44.4%. ROC analysis revealed HSP70 as the strongest predictor of conception failure (AUC = 0.93) with optimal cut-off of 8.5 ng/mL (sensitivity = 91.2%, specificity = 86.4%). The proposed Heat Stress Index achieved 91.8% accuracy for fertility prediction. Conclusion: This study provides the first integrated biomarker panel with validated cut-off values and a practical HSI scoring system for predicting reproductive failure in heat-stressed Awassi ewes. Breeding during THI > 80 should be avoided or accompanied by cooling interventions.
Keywords: Awassi ewes; heat stress; oxidative stress; HSP70; acute phase proteins; reproductive performance; predictive modelling